2021
DOI: 10.3389/fimmu.2021.651619
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive View on the Human Antibody Repertoire Against Staphylococcus aureus Antigens in the General Population

Abstract: Our goal was to provide a comprehensive overview of the antibody response to Staphylococcus aureus antigens in the general population as a basis for defining disease-specific profiles and diagnostic signatures. We tested the specific IgG and IgA responses to 79 staphylococcal antigens in 996 individuals from the population-based Study of Health in Pomerania. Using a dilution-based multiplex suspension array, we extended the dynamic range of specific antibody detection to seven orders of magnitude, allowing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 59 publications
(98 reference statements)
4
33
0
Order By: Relevance
“…21,30,31 Hla promotes blood coagulation via activation of human platelets. This phenomenon is independent of platelet killing, [32][33][34] and consistent with the strong procoagulatory PS exposure on the platelet membrane induced by Hla. In vivo, intravenous injection of Hla in mice induced platelet aggregation and formation of micro-thrombi.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…21,30,31 Hla promotes blood coagulation via activation of human platelets. This phenomenon is independent of platelet killing, [32][33][34] and consistent with the strong procoagulatory PS exposure on the platelet membrane induced by Hla. In vivo, intravenous injection of Hla in mice induced platelet aggregation and formation of micro-thrombi.…”
Section: Discussionsupporting
confidence: 78%
“…0.56 µM) compared to the Hla concentrations found in patient sera (up to 60 µM ). 34 While platelet activation by various S. aureus proteins like Clumping factor A (ClfA), SdrE, AtlA1, CHIPS, FLIPr, and Eap including Hla is well accepted, the consequences of platelet killing by S. aureus has gained less attention. 3,36 However, killing of platelets might be clinically highly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…All humans develop anti-S. aureus antibodies due to life-long exposure to S. aureus through nasal carriage or prior infections. However, the presence of antibodies does not confer protection against future infections and the antibody repertoire against S. aureus, especially in healthy individuals, is highly variable 116 . Elucidating pathogen-specific antibodies to S. aureus and understanding the functional role of the protective versus susceptible nature of an individual's antibody response is essential for the development of successful immunotherapies against S. aureus.…”
Section: Protective Versus Susceptible Immune Responses To S Aureusmentioning
confidence: 99%
“…93 S. aureus strains of AE patients but not laboratory strains were reported to accumulate in keratinocytes and induce IL-1alpha via TLR9, 94 further exacerbating the inflammation. It has been shown that different staphylococcal antigens cause individual response on the specific IgG and IgA production, 95 but also interactions between IgE and staphylococcal antigens like SEA, SEB or fibronectin have been reported to play a role in disease development by activating specific IgE-and T cellmediated immune responses. 96,97 In addition, it is also known that S. aureus can evade the T cell-mediated response at different steps and evades immunological memory which may have implications on vaccine development.…”
Section: Immune Systemmentioning
confidence: 99%